Bayesian Network Based Services Recommendation - WU, J. (Institutional Knowledge at Singapore Management University, 2009)
Nowadays, how to efficiently compose Web services has become a hotspot. In this paper, we introduce a method of recommending an optimal service sequence based on the original service sequence for a composite service. This method uses a Bayesian-based approach and selects the service sequence that has the largest probability as the best choice. Compared with existing methods, this method has two advantages: firstly, service sequences recommended by this method are robust; secondly, this method produces a composite service with a high quality and it does this efficiently. We have conducted experiments to illustrate how our work helps facilitate Web service composition.